آراء أبي الحسن الأشعري في مسائل أصول الفقه وأثرها في اختياراته الكلامية = Abu al-Hasan al-Ash‘ari’s views on matters of Islamic legal theory and their bearing on his theological preferences - El-Mesawi, Mohamed El-Tahir; Salhab, Belal Barakat (International Institute of Islamic Thought, IIIT, 2019)
تُعنى هذه الدراسة بإبراز جانب مهم من التراث العلمي لأبي الحسن الأشعري (260-324هـ/874-936م) لم ينل حظه من البحث، وهو الجانب الـمتعلِّق بالعلاقة الجدلية التفاعلية عنده بين النظر في مسائل علم أصول الفقه والبحث في قضايا علم الكلام، من أجل الكشف عن أثر آرائه في الأول في توجيه مذاهبه في الثاني. وقد سلكت الدراسة في ذلك منهجاً يقوم على استنطاق نصوص الأشعري نفسه، وعدم التعويل على ما نُسِب إليه في مصنَّفات علماء الأصول والكلام الـمتأخرين، باستثناء ابن فورك الذي يُعَدُّ كتابه "مقالات الأشعري" مصدراً أولياً لفكر الأشعري بعد مصنَّفات هذا الأخير الثابتة نسبتها إليه. أمّا مناط التركيز في الدراسة فهو مباحث الجانب الأصولي اللغوي كما يتجلّى في تلك الـمصادر الأولية. الكلمات الـمفتاحية: الأشعري، علم أصول الفقه، علم الكلام، جدل العلاقة بين علم أصول الفقه وعلم الكلام. ******************************************************************************* This study is concerned with bringing to light an important, but understudied, aspect of the scholarly legacy of Abu al-Hasan al-Ash‘ari (260-324H/874-936CE), namely the dialectical and interactive relationship between the inquiry of issues of Islamic legal theory and investigation into questions of Islamic theology. The aim is to see how al-Ash‘ari’s views in legal theory shaped his opinions in theology. For this the study followed a methodological approach consisting of engaging with al-Ash‘ari’s texts themselves with resorting to what has been attributed to him in the works of later Muslim legal theorists and theologians, to the exception of Ibn Furak’s Maqalat al-Ash‘ari which stands as a primary source next to al-Ash‘ari’s works whose attribution to is beyond doubt. The study has focused on fundamental issues pertaining to legal theory as expounded in those primary sources. Keywords: al-Ash‘ari, Islamic legal theory, Islamic theology, dialectics of legal theory and theology.